Automation of libraries in Nigeria: the preliminaries, implications and constraints (2005)
This work is about automation of libraries in Nigeria. The paper delved into the history of library automation and outlines the preliminaries necessary before any automation initiatives are taken. The implications of such initiatives on the library/institution, staff and users are highlighted. Furthermore, the paper identified various constraints to the automation initiatives in Nigeria libraries today. However, the paper concluded and made recommendations on how Nigeria libraries can enhance their automation efforts.